2017
DOI: 10.1051/0004-6361/201730588
|View full text |Cite
|
Sign up to set email alerts
|

“TNOs are Cool”: A survey of the trans-Neptunian region

Abstract: Context. Gravitationally bound multiple systems provide an opportunity to estimate the mean bulk density of the objects, whereas this characteristic is not available for single objects. Being a primitive population of the outer solar system, binary and multiple trans-Neptunian objects (TNOs) provide unique information about bulk density and internal structure, improving our understanding of their formation and evolution. Aims. The goal of this work is to analyse parameters of multiple trans-Neptunian systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
2
13
0
1
Order By: Relevance
“…Our density estimate of P-type (87) Sylvia (Carry et al 2021) as well as that of (107) Camilla (Pajuelo et al 2018) appear compatible with those of several D ≤ 300 km TNOs (Brown 2013;Kovalenko et al 2017) providing support for a direct link between P/D types and TNOs. However, the same applies for C-type asteroids.…”
Section: P-typessupporting
confidence: 68%
See 2 more Smart Citations
“…Our density estimate of P-type (87) Sylvia (Carry et al 2021) as well as that of (107) Camilla (Pajuelo et al 2018) appear compatible with those of several D ≤ 300 km TNOs (Brown 2013;Kovalenko et al 2017) providing support for a direct link between P/D types and TNOs. However, the same applies for C-type asteroids.…”
Section: P-typessupporting
confidence: 68%
“…Based on our density estimates for all C-complex bodies, we cannot discard a link between these asteroid types and current TNOs. We note the existence of a few TNOs with extremely low densities (Brown 2013;Kovalenko et al 2017) whose counterparts were not identified by our survey of main-belt asteroids.…”
Section: P-typesmentioning
confidence: 64%
See 1 more Smart Citation
“…As 2007 OR 10 is a fairly large object, internal porosity is likely negligible and a lower limit for the density can be set to 1.2 g cm −3 , a typical value for medium size TNOs (Brown 2013;Barr & Schwamb 2016;Kovalenko et al 2017). For an upper limit we use the densities of the largest dwarf planets Pluto and Eris, and adopt 2.5 g cm −3 .…”
Section: Possible Orbits Of the Satellitementioning
confidence: 99%
“…Cryovolcanism on mid-sized TNOs is an intriguing prospect, as these objects are generally deemed too small to sustain any geophysical activity. Models suggest that some TNOs may be differentiated owing to the right combination of size and density (Merk and Prialnik, 2006;McKinnon et al, 2008;Guilbert-Lepoutre et al, 2011;Shchuko et al, 2014; Malamud and Prialnik, 90377 Sedna Lykawka and Mukai, 2005;Trujillo et al, 2005;Emery et al, 2007;Stansberry et al, 2008;Barucci et al, 2010;Lellouch et al, 2013;Braga-Ribas et al, 2014225088 2007OR 10 Tancredi, 2010Brown et al, 2011aBrown et al, , 2012Santos-Sanz et al, 2012;Pál et al, 2016;Holler et al, 2017;Kiss et al, 201790482 Orcus Fornasier et al, 2004bde Bergh et al, 2005;Lykawka and Mukai, 2005;Trujillo et al, 2005;Brown and Suer, 2007;Barucci et al, 2008;Stansberry et al, 2008;Delsanti et al, 2010;DeMeo et al, 2010;Carry et al, 2011;Thirouin et al, 2014;Brown andButler, 2017, 2018;Kovalenko et al, 2017 50000 Quaoar Brown and Trujillo, 2004;Jewitt and Luu, 2004;Lykawka and Mukai, 2005;Brown and Suer, 2007;Schaller and Brown, 2007b;Stansberry et al, 2008;…”
Section: Differentiation and Cryovolcanismmentioning
confidence: 99%